Enhancing Educational Financing Efficiency through Renewable Energy Integration: A Case Study of Solar Power Utilization at School - Adawiyah, Miftahul; Ahmad, Zainal Arifin; Munawwar , Fabroy Fauziyatul; Kurniawan , Ilham (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2025)
As educational institutions worldwide face increasing pressure to deliver quality education amid limited budgets, infrastructure management and energy efficiency have become critical concerns. This study explores how the integration of solar photovoltaic (PV) systems can serve as a strategic tool to improve education financing efficiency, using Muhammadiyah 1 Junior High School (SMP) Berbah in Indonesia as a case study. Employing a qualitative case study method, this research analyzes planning, implementation, and management processes of solar PV systems in the school’s infrastructure. Findings indicate that although the solar power plant has not yet reached optimal savings, its integration supports operational cost reductions, aligns with environmental goals, and enhances long-term financial planning. The study underscores the importance of infrastructure-based energy strategies and recommends wider adoption of solar PV in educational settings, complemented by audits, stakeholder partnerships, and curriculum integration on sustainability. Despite its local focus, the study highlights scalable practices for schools globally, while acknowledging limitations in generalizability and long-term performance tracking. Future research should examine broader contexts and policy variables to strengthen the evidence base for renewable energy in education.